Static Simulation of Speed Bump Structure Alloy Concrete Foam And Polymeric Foam With 1, 2 And 3 Inch Cavity Variations Using Ansys 14.5 Software - Dino Hastrino (Trigin Publisher, 2022)
Speed bump (vehicle speed limiter) is elevated sections of road in the form of additional asphalt or cement that are strung across the street for a sign of slow down. Functions that enhance safety for users jalan.Material to manufacture high speed bumprelatif this cause expensive production costs and the impact on the selling price and therefore new dilakukanPenelitian of natural fiber from oil palm empty fruit bunches (EFB). Abundant raw materials due to oil palm empty fruit bunches (EFB) often become waste is estimated to be quite economical and developed into an environmentally friendly alternative material. The purpose of this study is to simulate the static loading on the speed bump of foam concrete materials and fiber reinforced polymeric foam EFB using Ansys 14.5 software. in this study specimens to be tested 10 models and simulated static on the upper side to determine the stress distribution at the speed bump. Speed bump modeled using SolidWorks software in 2012 and was simulated using ANSYS software compared to 14.5 for voltage distribution. In this study, found that of the static simulation results at top speed bump we concluded that the total minimum voltage deformation occurs in the model bump with casing of 0.94628mm speed and maximum voltage contained in the model of speed bump of 3 inches of concrete 1,2343mm, Equivalent Elastic Strain the minimum speed bump 1 contained in the model of 0.013427 inches, and Equivalent Elastic maximum strain contained in the model of speed bump with a casing of 0.023304, while the minimum Maximum Principal Stress contained in model 3 inches of concrete speed bump for 0.002801Mpa, and Maximum Principal Stress maximum contained in the model speed bump with a casing of 0.016959MPa.